Does Inner Awareness Always Accompany Outer Awareness During Perception? - Chaturvedi, Madhu Mangal; Ravishankar Sarma, A. V. (Problemos, 2019)
In the present paper, we defend the thesis that outer-world-directed perceptual consciousness is always accompanied by an inner awareness (IAOA). This is contrary to the view that outer-world-directed conscious mental states are not accompanied by an inner awareness, which is held by Gennaro (2008) against Kriegel’s (2009a and 2009b) self-representationalism. We attempt to show why philosophers like Gennaro get it wrong when they deny the IAOA thesis by critically examining his arguments against it and by giving arguments in its favour.
Keywords: Inner Awareness; Perceptual Consciousness; Self-representationalism; Higher-Order-Thought